Prkar1a in the Regulation of Insulin Secretion - Hussain, M. A.; Stratakis, C.; Kirschner, L. (Hormone and Metabolic Research, 2012)
The incidence of type 2 diabetes mellitus (T2DM) is rapidly increasing worldwide with significant consequences on individual quality of life as well as economic burden on states’ healthcare costs. While origins of the pathogenesis of T2DM are poorly understood, an early defect in glucose-stimulated insulin secretion (GSIS) from pancreatic β-cells is considered a hallmark of T2DM 1.Upon a glucose stimulus, insulin is secreted in a biphasic manner with an early first-phase burst of insulin, which is followed by a second, more sustained phase of insulin output 2. First phase insulin secretion is diminished early in T2DM as well is in subjects who are at risk of developing T2DM 3456.An effective treatment of T2DM with incretin hormone glucagon-like peptide-1 (GLP-1) or its long acting peptide analogue exendin-4 (E4), restores first-phase and augments second-phase glucose stimulated insulin secretion. This effect of incretin action occurs within minutes of GLP-1/E4 infusion in T2DM humans. An additional important consideration is that incretin hormones augment GSIS only above a certain glucose threshold, which is slightly above the normal glucose range. This ensures that incretin hormones stimulate GSIS only when glucose levels are high, while they are ineffective when insulin levels are below a certain threshold 78.Activation of the GLP-1 receptor, which is highly expressed on pancreatic β-cells, stimulates 2 distinct intracellular signaling pathways: a) the cAMP-protein kinase A branch and b) the cAMP-EPAC2 (EPAC=exchange protein activated by cAMP) branch. While the EPAC2 branch is considered to mediate GLP-1 effects on first-phase GSIS, the PKA branch is necessary for the former branch to be active 910. However, how these 2 branches interplay and converge and how their effects on insulin secretion and insulin vesicle exocytosis are coordinated is poorly understood.Thus, at the outset of our studies we have a poorly understood intracellular interplay of cAMP-dependent signaling pathways, which – when stimulated – restore glucose-dependent first phase and augment second phase insulin secretion in the ailing β-cells of T2DM.
Keywords: type 2 diabetes; Prkar1a; insulin secretion